2020
DOI: 10.26719/emhj.20.066
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco price increase and consumption behaviour among male smokers in Saudi Arabia: a community-based study

Abstract: Background: Saudi Arabia doubled its tobacco tax in June 2017. Aims: To examine the association between an increase in tobacco prices and consumption behaviour among current male smokers in Riyadh. Methods: We conducted a community-based study using a self-administered questionnaire distributed to current male smokers aged 15+ years in Riyadh in 2018. The survey included questions on sociodemographic characteristics, tobacco consumption and self-reported chronic health conditions. Results: A total of 1481 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…They concluded that there was sufficient evidence to support increases in taxes to achieve a decline in overall and adult tobacco use, induce current users to quit, and reduce the prevalence of use among young people. 27 , 28 Our results are also consistent with a local study published in 2020 29 , 30 and other econometric studies performed in various countries which concluded that tax increases had a significant impact on smoking cessation, especially among heavy smokers, and effectively reduced cigarette use. 31 , 32 A 2014 systematic review of 77 reports, updated in 2020 with 68 additional studies, concluded that a tax-based strategy is, comparatively, one of the most effective measures to achieve the goal of reducing cigarette consumption.…”
Section: Discussionsupporting
confidence: 89%
“…They concluded that there was sufficient evidence to support increases in taxes to achieve a decline in overall and adult tobacco use, induce current users to quit, and reduce the prevalence of use among young people. 27 , 28 Our results are also consistent with a local study published in 2020 29 , 30 and other econometric studies performed in various countries which concluded that tax increases had a significant impact on smoking cessation, especially among heavy smokers, and effectively reduced cigarette use. 31 , 32 A 2014 systematic review of 77 reports, updated in 2020 with 68 additional studies, concluded that a tax-based strategy is, comparatively, one of the most effective measures to achieve the goal of reducing cigarette consumption.…”
Section: Discussionsupporting
confidence: 89%
“…In June 2017, Saudi Arabia doubled its tobacco tax, resulting in a significant reduction in cigarette consumption [21]. While this has been a significant step in the right direction, the need for smoking cessation support is clear, with only 4% of attempts to quit tobacco successful without support; this number is doubled by professional support and proven cessation medication intervention [17,18].…”
mentioning
confidence: 99%